High weatherability fluorine-containing acrylic composite coating and preparation method thereof

A fluorinated emulsion is formed by polymerizing 2-difluoromethyl acrylate with other monomers, and then combined with nano-SiO2 to prepare a high-weather-resistant fluorinated acrylic coating. This solves the problems of poor toughness at low temperatures and film formation at high temperatures in existing coatings, and improves both weather resistance and economy. It is suitable for a variety of substrates.

CN120818275BActive Publication Date: 2025-11-18AMBASSADOR PAINT (ANHUI) CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511325875.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-17
Publication Date
2025-11-18
Estimated Expiration
2045-09-17

AI Technical Summary

Technical Problem

Existing fluorinated acrylic coatings have poor toughness at low temperatures, their weather resistance depends on high fluorine content, and they are costly. Traditional water-based coatings require high-temperature sintering to form a film, which limits their application range and economic efficiency.

Method used

A fluorinated emulsion was formed by polymerizing 2-difluoromethyl ethyl acrylate (DFMAET) with methyl methacrylate, butyl acrylate and glycidyl methacrylate, and then combined with titanium dioxide and nano-SiO2 to prepare a high-weather-resistant fluorinated acrylic coating without baking. Soap-free emulsion polymerization was used to form an inorganic-organic hybrid network, which enhanced the salt spray resistance.

Benefits of technology

It improves the weather resistance and economy of the coating, reduces energy consumption, is suitable for a variety of substrates, requires no baking, is suitable for use in sensitive environments, has anti-mildew adhesion properties, and is low in cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120818275B_ABST
    Figure CN120818275B_ABST
Patent Text Reader

Abstract

The application relates to the field of fluorine-containing coatings and discloses a high-weather-resistance fluorine-containing acrylic composite coating and a preparation method thereof. The high-weather-resistance fluorine-containing acrylic composite coating is prepared by emulsion polymerization of 2-difluoromethyl-acrylic acid ethyl ester (DFMAET) as a main raw material, methyl methacrylate (MMA), butyl acrylate (BA) and glycidyl methacrylate (GMA). The fluorine-containing acrylic composite coating comprises, by mass percentage, 56-64% of fluorine-containing emulsion, 14-18% of titanium white powder (R type), 6-10% of nano-SiO 2 2-2.8% of film-forming aids, 0.16-0.24% of defoaming agents, 0.2-0.4% of thickening agents and deionized water, and the balance is 100%. Compared with traditional acrylate coatings and fluorocarbon coatings, the coating has the advantages of high weather resistance, low surface energy, balanced mechanical properties, economy and environmental protection, and the like. The coating has the effects of resisting ultraviolet light and salt spray corrosion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of fluorinated coatings, and particularly relates to a high weather-resistant fluorinated acrylic composite coating and its preparation method. Background Technology

[0002] Coatings have gradually developed towards greater variety, greener standards, more functional products, higher efficiency, and greater reliability. Traditional solvent-based coatings are being replaced by more environmentally friendly water-based coatings, which have a very promising future.

[0003] Fluoropolymers are high-molecular materials with many unique structures, resulting in numerous special properties. In fluorocarbon coatings, the electronegativity of fluorine (F) is extremely high, and its atomic radius is small. Due to the presence of short, FC bonds in the molecule, the bond energy is very high, exhibiting excellent stability against light, heat, and chemical effects, providing excellent protection. Therefore, fluorocarbon coatings possess outstanding performance in coating applications. Compared to acrylic and polyurethane coatings, fluorocarbon coatings demonstrate superior adhesion, solvent resistance, self-cleaning properties, weather resistance, and other durability.

[0004] Waterborne fluorocarbon acrylic coatings primarily consist of PVDF, polymerized from polyvinylidene fluoride. It represents an environmentally friendly upgrade from solvent-based fluorocarbon coatings, combining the high performance of fluorocarbon resins with the green characteristics of waterborne systems. Polyvinylidene fluoride (PVDF) is a semi-crystalline fluorinated polymer that possesses both the weather resistance of fluoropolymers and the mechanical properties of engineering plastics, making it widely used in high-end manufacturing, construction, and energy sectors. However, PVDF suffers from drawbacks such as brittleness, the need for high-temperature sintering to form a film, and high cost. Currently, most fluorinated acrylic coatings use β-fluorine-substituted monomers such as trifluoroethyl methacrylate (TFEMA). When TFEMA is copolymerized with hard monomers (such as MMA), the temperature gradient (Tg) easily rises to 50-70℃. Below this temperature, the coating film enters a glassy state, restricting chain movement. Trifluoroethyl has significant steric hindrance, resulting in tightly packed molecular chains and a sharp decrease in toughness at low temperatures (<0℃). Summary of the Invention

[0005] The present invention aims to provide a high weather-resistant fluorinated acrylic composite coating and its preparation method. The high weather-resistant fluorinated acrylic composite coating is obtained by emulsion polymerization of 2-difluoromethyl ethyl acrylate (DFMAET), methyl methacrylate (MMA), butyl acrylate (BA), and glycidyl methacrylate (GMA).

[0006] This invention uses ethyl acrylate as a substrate, activates the α-position of ethyl acrylate with a strong base, and undergoes a nucleophilic substitution reaction with difluoromethyl bromide (BrCF2H) to obtain the 2-difluoromethyl-ethyl acrylate monomer. 2-Difluoromethyl-ethyl acrylate, methyl methacrylate, butyl acrylate, and glycidyl methacrylate are polymerized to obtain a fluorinated emulsion. This fluorinated emulsion, along with titanium dioxide, nano-SiO2, film-forming aids, defoamers, and thickeners, is used to prepare a highly weather-resistant fluorinated acrylic composite coating. Compared with traditional acrylic coatings and fluorinated coatings, this coating has advantages such as high weather resistance and economic and environmental benefits. The structure of the 2-difluoromethyl-ethyl acrylate monomer is as follows:

[0007] .

[0008] The preparation method for the above-mentioned high weather-resistant fluorinated acrylic composite coating, wherein the preparation of 2-difluoromethyl acrylate (DFMAET) includes the following steps:

[0009] S1. Equipped with a four-necked flask including a mechanical stirrer, condenser, and constant pressure dropping funnel, with nitrogen protection throughout the process;

[0010] S2. Dissolve ethyl acrylate in tetrahydrofuran, add to a four-necked flask, cool in an ice bath, add NaH, and stir until the bubbles completely disappear to form sodium α-enol intermediate;

[0011] S3. Add difluoromethyl bromide through a dropping funnel. After the addition is complete, allow the temperature to rise naturally to reflux. Monitor the reaction endpoint by TLC to obtain the reaction solution.

[0012] S4. After cooling the reaction solution, quench it with saturated ammonium chloride solution, extract with dichloromethane, combine the organic phases, dry with anhydrous sodium sulfate, filter, and remove the solvent by vacuum distillation to obtain the crude product; pass the crude product by silica gel column chromatography, collect the fraction with Rf=0.5, and distill under vacuum to obtain ethyl 2-difluoromethyl acrylate.

[0013] Preferably, in step S2, the molar ratio of ethyl acrylate to NaH is 1:(1-1.5); the ratio of tetrahydrofuran to ethyl acrylate is (45-55) mL:100 mmol; and the ice bath is cooled to -5 to -15°C.

[0014] Preferably, the molar ratio of difluoromethyl bromide to ethyl acrylate is (1-1.2):1; difluoromethyl bromide is dissolved in an equal amount of tetrahydrofuran as S2; the addition flow rate is 0.3-0.7 mL / min; the reflux temperature is 60-70℃, and the reaction time is 10-18 h; the TLC monitoring uses petroleum ether and ethyl acetate as the developing solvent, with a volume ratio of petroleum ether to ethyl acetate of (4-8):1, a product Rf of 0.5, and a starting material Rf of 0.7; the reaction endpoint is the disappearance of the substrate spot, with only the product spot remaining.

[0015] Preferably, the amount of saturated ammonium chloride solution added is 150-300 mL of saturated ammonium chloride solution per 100 mmol of ethyl acrylate; the amount of dichloromethane used each time is 50-75 mL per 100 mmol of ethyl acrylate; anhydrous sodium sulfate is used for drying for 4-8 hours; the silica gel is 200-300 mesh; the eluent is petroleum ether and ethyl acetate, and the volume ratio of petroleum ether to ethyl acetate is (6-10):1.

[0016] The preparation method of the high weather-resistant fluorinated acrylic composite coating includes the following steps:

[0017] T1. Add ethyl 2-difluoromethyl acrylate, methyl methacrylate, butyl acrylate, and glycidyl methacrylate to a beaker in a certain proportion and stir mechanically until they are mixed evenly to obtain a monomer mixture; dissolve DNS-86 and OP-10 in deionized water and disperse ultrasonically until transparent to obtain an emulsifier aqueous solution; add the monomer mixture to the emulsifier aqueous solution and stir to form a stable pre-emulsion;

[0018] T2. A four-necked flask is equipped with a stirrer, a condenser, a dropping funnel, and a thermometer. The flask is purged with nitrogen three times. The first portion of the preemulsion, the first portion of the ammonium persulfate solution, and deionized water are added to the flask. The mixture is heated and stirred. When the system shows a blue light, the second portion of the preemulsion and the second portion of the ammonium persulfate solution are added dropwise simultaneously.

[0019] T3. After the addition is complete, keep the reaction at the temperature. After cooling, adjust the pH with ammonia water and remove trace amounts of unreacted monomers by vacuum distillation to obtain a fluorinated emulsion.

[0020] T4. Add titanium dioxide and nano-SiO2 to the first part of deionized water, disperse in a high-speed disperser, add fluorinated emulsion, film-forming aid and the first part of defoamer in sequence and stir, add thickener to adjust viscosity, add the second part of defoamer and the second part of deionized water, stir and filter through a filter screen to remove gel particles, and obtain a high weather-resistant fluorinated acrylic composite coating.

[0021] Preferably, in step T1, the mass ratio of ethyl 2-difluoromethyl acrylate, methyl methacrylate, butyl acrylate, and glycidyl methacrylate is (4-6):(6-8):(4-6):(2-4); the mechanical stirring speed is 300-800 rpm for 8-15 min; the mass ratio of DNS-86 to ethyl 2-difluoromethyl acrylate is 1:(10-15); the mass ratio of DNS-86 to OP-10 is 1:(0.2-0.6); and the stirring speed is 1500-2500 rpm for 30-50 min.

[0022] Preferably, in step T2, the mass ratio of the first preemulsion, deionized water, and the first ammonium persulfate solution is 5:(6-10):(0.25-0.5); the first ammonium persulfate solution is an aqueous solution with a mass concentration of 2-4%; the temperature is raised to 70-80℃ at a rate of 5℃ / min; the stirring speed is 300 rpm; the mass ratio of the second preemulsion and the second ammonium persulfate solution is 6:(0.7-1.4), and the dropping rate of the second preemulsion is 1-3 mL / min; the second ammonium persulfate solution is an aqueous solution with a mass concentration of 2-4%, and the dropping rate of the second ammonium persulfate solution is 0.5-1.5 mL / min.

[0023] Preferably, in T3, the heat preservation temperature is 80-90℃ and the time is 1-2h; the temperature after cooling is 35-45℃; the ammonia water is an aqueous solution with a mass concentration of 5-15% and the pH is adjusted to 8.5; the vacuum distillation is carried out under the conditions of -0.08MPa and 35-45℃.

[0024] Preferably, in T4, the mass ratio of titanium dioxide, nano-SiO2, and the first portion of deionized water is (7-9):(1-3):(3-5); the high-speed disperser operates at 2000-4000 rpm for 15-25 min; the mass ratio of the fluorinated emulsion, film-forming aid, and the first portion of defoamer is 150:(5-6):(0.2-0.3); the stirring speed is 300-800 rpm; the thickener is hydroxyethyl cellulose, and the mass ratio of hydroxyethyl cellulose to the fluorinated emulsion is (0.5-1.0):150; the amount of the second portion of defoamer is equal to that of the first portion of defoamer; the mass ratio of the second portion of deionized water to the fluorinated emulsion is (269.1-276.4):150; and the filter screen is 100 mesh.

[0025] Compared with the prior art, the beneficial effects of the present invention are reflected in:

[0026] (1) In traditional fluorinated acrylic coatings, the fluorine atom is located at the distal end of the ester group, resulting in weak UV protection for the double bond, and weather resistance depends on high fluorine content. This coating uses ethyl acrylate as a substrate, and a strong base activates the α-position of ethyl acrylate, which undergoes a nucleophilic substitution reaction with difluoromethyl bromide (BrCF2H) to obtain the 2-difluoromethyl-ethyl acrylate monomer. The difluoromethyl group (-CF2H) at the α-position directly connects to the ortho position of the double bond, forming a short-range shielding effect, which improves the absorption rate of ultraviolet light in the 300-400nm range. Under the same fluorine content, the weather resistance surpasses that of traditional coatings. The introduction of difluoromethyl group (-CF2H) significantly changes the electron cloud distribution and steric hindrance of the molecule. The hydrophobicity of the difluoromethyl group gives the material low surface energy, making it suitable for anti-mildew materials.

[0027] (2) A fluorinated emulsion is obtained by polymerizing 2-difluoromethyl ethyl acrylate (DFMAET), methyl methacrylate (MMA), butyl acrylate (BA), and glycidyl methacrylate (GMA). The nanoparticles are bonded to the epoxy groups of GMA to form an "inorganic-organic hybrid network," which enhances its salt spray resistance. The epoxy groups of GMA form covalent bonds with concrete (hydroxyl groups) and metals (oxides), making it particularly suitable for polar substrates (such as concrete and aluminum alloys), without the need for primer treatment. Soap-free emulsion polymerization is used, resulting in no free emulsifier residue and low formaldehyde release, making it suitable for sensitive environments such as hospitals and schools. Furthermore, no baking is required, reducing energy consumption. This coating is characterized by its low price, high weather resistance, and environmental friendliness. Attached Figure Description

[0028] Figure 1 The structural diagram of ethyl 2-difluoromethyl acrylate monomer;

[0029] Figure 2 This is a physical image of the high weather-resistant fluorinated acrylic composite coating from Example 4. Detailed Implementation

[0030] The following embodiments are only used to illustrate the technical solutions of the present invention more clearly, and should not be used to limit the scope of protection of the present invention.

[0031] The main compounds used in the examples and comparative examples were all commercially available products and were not subjected to any further purification treatment.

[0032] Example 1

[0033] The synthesis of ethyl 2-difluoromethyl acrylate (DFMAET) includes the following steps:

[0034] S1. Equipped with a four-necked flask including a mechanical stirrer, condenser, and constant-pressure dropping funnel, with nitrogen protection throughout the process.

[0035] S2. Dissolve 100 mmol of ethyl acrylate in 50 mL of THF, add to a four-necked flask, cool to -10 °C in an ice bath, add 120 mmol of NaH, and stir until the bubbles completely disappear to form the sodium α-enol intermediate.

[0036] S3. Dissolve 110 mmol BrCF2H in 50 mL THF and slowly add it through a dropping funnel at a flow rate of 0.5 mL / min. After the addition is complete, allow the mixture to heat naturally to reflux. Monitor the reaction endpoint by TLC to obtain the reaction solution (TLC monitoring, developing solvent volume ratio: petroleum ether: ethyl acetate = 6:1, product Rf = 0.5, starting material Rf = 0.7).

[0037] S4. After cooling the reaction solution, 200 mL of saturated ammonium chloride solution was slowly poured in to quench the reaction. The mixture was extracted three times with 60 mL of dichloromethane. The organic phases were combined, dried over anhydrous sodium sulfate for 6 hours, filtered, and the solvent was removed by vacuum distillation to obtain the crude product. The crude product was subjected to silica gel column chromatography at a 250-mesh screen with an eluent volume ratio of petroleum ether to ethyl acetate of 8:1. The fraction with Rf = 0.5 was collected and distilled under reduced pressure to give ethyl 2-difluoromethyl acrylate. The yield was calculated.

[0038] Example 2

[0039] The synthesis of ethyl 2-difluoromethyl acrylate (DFMAET) includes the following steps:

[0040] S1. Equipped with a four-necked flask including a mechanical stirrer, condenser, and constant-pressure dropping funnel, with nitrogen protection throughout the process.

[0041] S2. Dissolve 100 mmol of ethyl acrylate in 45 mL of THF, add to a four-necked flask, cool to -5 °C in an ice bath, add 100 mmol of NaH, and stir until the bubbles completely disappear to form the sodium α-enol intermediate.

[0042] S3. Dissolve 100 mmol BrCF2H in 50 mL THF and slowly add it through a dropping funnel at a flow rate of 0.3 mL / min. After the addition is complete, allow the mixture to heat naturally to reflux. Monitor the reaction endpoint by TLC to obtain the reaction solution (TLC monitoring, developing solvent volume ratio: petroleum ether: ethyl acetate = 4:1, product Rf = 0.5, starting material Rf = 0.7).

[0043] S4. After cooling the reaction solution, quench it with 150 mL of saturated ammonium chloride solution. Extract three times with 50 mL of dichloromethane. Combine the organic phases, dry with anhydrous sodium sulfate for 4 h, filter, and remove the solvent by vacuum distillation to obtain the crude product. Analyze the crude product onto a 200-mesh silica gel column with an eluent volume ratio of petroleum ether:ethyl acetate = 6:1. Collect the fraction with Rf = 0.5, and distill under reduced pressure to give ethyl 2-difluoromethyl acrylate. Calculate the yield.

[0044] Example 3

[0045] The synthesis of ethyl 2-difluoromethyl acrylate (DFMAET) includes the following steps:

[0046] S1. Equipped with a four-necked flask including a mechanical stirrer, condenser, and constant-pressure dropping funnel, with nitrogen protection throughout the process.

[0047] S2. Dissolve 100 mmol of ethyl acrylate in 55 mL of THF, add to a four-necked flask, cool to -15 °C in an ice bath, add 150 mmol of NaH, and stir until the bubbles completely disappear to form the sodium α-enol intermediate.

[0048] S3. Dissolve 120 mmol BrCF2H in 50 mL THF and slowly add it through a dropping funnel at a flow rate of 0.7 mL / min. After the addition is complete, allow the mixture to heat naturally to reflux. Monitor the reaction endpoint by TLC to obtain the reaction solution (TLC monitoring, developing solvent volume ratio: petroleum ether: ethyl acetate = 8:1, product Rf = 0.5, starting material Rf = 0.7).

[0049] S4. After cooling the reaction solution, quench it with 300 mL of saturated ammonium chloride solution. Extract three times with 75 mL of dichloromethane. Combine the organic phases, dry with anhydrous sodium sulfate for 8 h, filter, and remove the solvent by vacuum distillation to obtain the crude product. Analyze the crude product onto a 300-mesh silica gel column with an eluent volume ratio of petroleum ether:ethyl acetate = 10:1. Collect the fraction with Rf = 0.5, and distill under reduced pressure to give ethyl 2-difluoromethyl acrylate. Calculate the yield.

[0050] Example 4

[0051] A method for preparing a high weather-resistant fluorinated acrylic composite coating includes the following steps:

[0052] T1. Add 25g of DFMAET, 35g of MMA, 25g of BA, and 15g of GMA to a beaker and mechanically stir at 500rpm for 10min until homogeneous to obtain a monomer mixture. Dissolve 2g of DNS-86 and 0.8g of OP-10 in 100mL of deionized water and ultrasonically disperse until a clear solution is obtained to obtain an emulsifier aqueous solution. Slowly pour the monomer mixture into the emulsifier aqueous solution, and simultaneously start a high-shear emulsifier (IKA T25) at 2000rpm, homogenize for 40min to form a stable pre-emulsion. The system is milky white and shows blue light reflection under strong light.

[0053] T2. A four-necked flask is equipped with a stirrer, a condenser, a dropping funnel, and a thermometer. The flask is purged with nitrogen three times. Add 50g of preemulsion, 4g of 2.5% APS solution, and 80g of deionized water to the flask. Heat to 75℃ at 5℃ / min, then stir at 300rpm. When the system exhibits blue light, simultaneously add 150g of preemulsion and 28g of 2.5% APS solution at a dropping rate of 2mL / min and 1mL / min, respectively, to avoid temperature fluctuations.

[0054] T3. After the addition is complete, the reaction is kept at 85℃ for 1.5h. After cooling to 40℃, the pH is adjusted to 8.5 with 10% ammonia water. The trace amount of unreacted monomer is removed by vacuum distillation at -0.08MPa and 40℃ to obtain 150g of fluorinated emulsion.

[0055] T4. Add 40g titanium dioxide and 10g nano-SiO2 to 20g deionized water, disperse at 3000rpm for 20min using a high-speed disperser, then add 150g fluorinated emulsion, 6g film-forming aid Texanol, and 0.25g defoamer BYK-028 sequentially, stirring at low speed. Add 0.7g hydroxyethyl cellulose to adjust the viscosity, then add 0.25g defoamer and 22.8g deionized water. After stirring, filter through a 100-mesh filter to remove gel particles, obtaining a high-weather-resistant fluorinated acrylic composite coating (e.g., ...). Figure 2 (As shown).

[0056] Example 5

[0057] A method for preparing a high weather-resistant fluorinated acrylic composite coating includes the following steps:

[0058] T1. Add 20g of DFMAET, 30g of MMA, 30g of BA, and 20g of GMA to a beaker and mechanically stir at 300rpm for 15min until homogeneous to obtain a monomer mixture. Dissolve 2g of DNS-86 and 0.4g of OP-10 in 100mL of deionized water and ultrasonically disperse until a clear solution is obtained to obtain an emulsifier aqueous solution. Slowly pour the monomer mixture into the emulsifier aqueous solution, and simultaneously start a high-shear emulsifier (IKAT25) at 1500rpm for 50min to form a stable pre-emulsion. The system is milky white and shows blue light reflection under strong light.

[0059] T2. A four-necked flask is equipped with a stirrer, a condenser, a dropping funnel, and a thermometer. The flask is purged with nitrogen three times. Add 50g of pre-emulsion, 5g of 2% APS solution, and 100g of deionized water to the flask. Heat the flask to 80℃ at 5℃ / min, then stir at 400rpm. When the system exhibits blue light, simultaneously add 150g of pre-emulsion and 35g of 2% APS solution at a dropping rate of 1mL / min and 1.5mL / min, respectively, to avoid temperature fluctuations.

[0060] T3. After the addition is complete, the reaction is kept at 80℃ for 2 hours. After cooling to 35℃, the pH is adjusted to 8.5 with 5% ammonia water. The trace amount of unreacted monomer is removed by vacuum distillation at -0.08MPa and 35℃ to obtain 150g of fluorinated emulsion.

[0061] T4. Add 35g titanium dioxide and 15g nano SiO2 to 15g deionized water, disperse at 2000rpm for 25min using a high-speed disperser, then add 150g fluorinated emulsion, 7g film-forming aid Texanol, and 0.3g defoamer BYK-028 in sequence and stir at low speed. Add 1.0g hydroxyethyl cellulose to adjust the viscosity, then add 0.3g defoamer and 26.4g deionized water. After stirring, filter through a 100-mesh filter to remove gel particles and obtain a high weather-resistant fluorinated acrylic composite coating.

[0062] Example 6

[0063] A method for preparing a high weather-resistant fluorinated acrylic composite coating includes the following steps:

[0064] T1. Add 30g of DFMAET, 40g of MMA, 20g of BA, and 10g of GMA to a beaker and mechanically stir at 800rpm for 8 minutes until homogeneous to obtain a monomer mixture. Dissolve 2g of DNS-86 and 1.2g of OP-10 in 100mL of deionized water and ultrasonically disperse until a clear solution is obtained to obtain an emulsifier aqueous solution. Slowly pour the monomer mixture into the emulsifier aqueous solution, and simultaneously start a high-shear emulsifier (IKAT25) at 2500rpm, homogenize for 30 minutes to form a stable pre-emulsion. The system is milky white and shows blue light reflection under strong light.

[0065] T2. A four-necked flask is equipped with a stirrer, a condenser, a dropping funnel, and a thermometer. The flask is purged with nitrogen three times. Add 50g of preemulsion, 2.5g of 4% APS solution, and 60g of deionized water to the flask. Heat to 70℃ at 5℃ / min, then stir at 200rpm. When the system exhibits blue light, simultaneously add 150g of preemulsion and 17.5g of 4% APS solution. The remaining preemulsion is added at a rate of 3mL / min, and the APS solution is added at a rate of 0.5mL / min to avoid temperature fluctuations.

[0066] T3. After the addition is complete, keep the reaction at 90℃ for 1 hour. After cooling to 45℃, adjust the pH to 8.5 with 15% ammonia water. Remove trace amounts of unreacted monomers by vacuum distillation at -0.08MPa and 45℃ to obtain 150g of fluorinated emulsion.

[0067] T4. Add 45g titanium dioxide and 5g nano SiO2 to 25g deionized water and disperse at 4000rpm for 15min using a high-speed disperser. Then, add 150g fluorinated emulsion, 5g film-forming aid Texanol, and 0.2g defoamer BYK-028 in sequence and stir at low speed. Add 0.5g hydroxyethyl cellulose to adjust the viscosity, then add 0.2g defoamer and 19.1g deionized water. After stirring, filter through a 100-mesh filter to remove gel particles and obtain a high weather-resistant fluorinated acrylic composite coating.

[0068] Comparative Example 1

[0069] The preparation of fluorinated acrylic composite coatings includes the following steps:

[0070] Add 25g of trifluoroethyl methacrylate (TFEMA), 35g of MMA, 25g of BA, and 15g of GMA to a beaker and mechanically stir at 500rpm for 10min until homogeneous. Dissolve 2g of DNS-86 and 0.8g of OP-10 in 100mL of deionized water and ultrasonically disperse until a clear solution is obtained to obtain an emulsifier aqueous solution. Slowly pour the monomer mixture into the emulsifier aqueous solution while simultaneously starting a high-shear emulsifier (IKA T25) at 2000rpm and homogenizing for 40min to form a stable pre-emulsion. The system is milky white and shows blue light reflection under strong light. A four-necked flask is equipped with a stirrer, condenser, dropping funnel, and thermometer, and purged with nitrogen three times. Add 50g of the pre-emulsion, 4g of 2.5% APS solution, and 80g of deionized water to the flask, heat to 75℃ at 5℃ / min, and then stir at 300rpm. When the system exhibited blue light, 150 g of the pre-emulsion and 28 g of 2.5% APS solution were simultaneously added dropwise. The remaining pre-emulsion was added at a rate of 2 mL / min, and the APS solution was added at a rate of 1 mL / min to avoid temperature fluctuations. After the addition was complete, the reaction was maintained at 85°C for 1.5 h. After cooling to 40°C, the pH was adjusted to 8.5 with 10% ammonia. Trace amounts of unreacted monomers were removed by vacuum distillation at -0.08 MPa and 40°C, yielding 150 g of fluorinated emulsion. Add 40g of titanium dioxide and 10g of nano-SiO2 to 20g of deionized water, disperse at 3000rpm for 20min using a high-speed disperser, then add 150g of fluorinated emulsion, 6g of film-forming aid Texanol, and 0.25g of defoamer BYK-028 in sequence and stir at low speed. Add 0.7g of hydroxyethyl cellulose to adjust the viscosity, then add 0.25g of defoamer and 22.8g of deionized water. After stirring, filter through a filter screen to remove gel particles and obtain a fluorinated acrylic composite coating.

[0071] Comparative Example 2

[0072] The preparation of 2-methyl-ethyl acrylate composite coating includes the following steps:

[0073] Add 25g of ethyl 2-methacrylate, 35g of MMA, 25g of BA, and 15g of GMA to a beaker and mechanically stir at 500rpm for 10min until homogeneous. Dissolve 2g of DNS-86 and 0.8g of OP-10 in 100mL of deionized water and ultrasonically disperse until a clear solution is obtained to obtain an emulsifier aqueous solution. Slowly pour the monomer mixture into the emulsifier aqueous solution while simultaneously starting a high-shear emulsifier (IKAT25) at 2000rpm and homogenizing for 40min to form a stable pre-emulsion. The system is milky white and shows blue light reflection under strong light. A four-necked flask is equipped with a stirrer, condenser, dropping funnel, and thermometer, and purged with nitrogen three times. Add 50g of the pre-emulsion, 4g of 2.5% APS solution, and 80g of deionized water to the flask, heat to 75℃ at 5℃ / min, and then stir at 300rpm. When the system exhibited blue light, 150 g of the pre-emulsion and 28 g of 2.5% APS solution were simultaneously added dropwise. The remaining pre-emulsion was added at a rate of 2 mL / min, and the APS solution was added at a rate of 1 mL / min to avoid temperature fluctuations. After the addition was complete, the reaction was maintained at 85°C for 1.5 h. After cooling to 40°C, the pH was adjusted to 8.5 with 10% ammonia. Trace amounts of unreacted monomers were removed by vacuum distillation at -0.08 MPa and 40°C, yielding 150 g of fluorinated emulsion. Add 40g of titanium dioxide and 10g of nano-SiO2 to 20g of deionized water, disperse at 3000rpm for 20min using a high-speed disperser, then add 150g of fluorinated emulsion, 6g of film-forming aid Texanol, and 0.25g of defoamer BYK-028 in sequence and stir at low speed. Add 0.7g of hydroxyethyl cellulose to adjust the viscosity, then add 0.25g of defoamer and 22.8g of deionized water. After stirring, filter through a filter screen to remove gel particles, thus obtaining a high weather-resistant fluorinated acrylic composite coating.

[0074] Comparative Example 3

[0075] Purchase PVDF coatings.

[0076] Comparative Example 4

[0077] The preparation of 2-difluoromethyl ethyl acrylate coating includes the following steps:

[0078] Dissolve 2g of DNS-86 and 0.8g of OP-10 in 100mL of deionized water and ultrasonically disperse until a clear solution is obtained to obtain an emulsifier aqueous solution. Slowly pour 100g of DFMAET into the emulsifier aqueous solution while simultaneously starting a high-shear emulsifier (IKA T25) at 2000 rpm and homogenizing for 40min to form a stable pre-emulsion. The system is milky white and shows blue light reflection under strong light. A four-necked flask is equipped with a stirrer, condenser, dropping funnel, and thermometer, and purged with nitrogen three times. Add 50g of pre-emulsion, 4g of 2.5% APS solution, and 80g of deionized water to the flask, heat to 75℃ at 5℃ / min, and stir at 300rpm. When the system shows blue light, simultaneously add the remaining 150g of pre-emulsion and 28g of 2.5% APS solution at a dropping rate of 2mL / min and 1mL / min to the APS solution to avoid temperature fluctuations. After the addition was complete, the reaction was maintained at 85℃ for 1.5 hours. After cooling to 40℃, the pH was adjusted to 8.5 with 10% ammonia. Trace amounts of unreacted monomers were removed by vacuum distillation at -0.08 MPa and 40℃ to obtain 150g of fluorinated emulsion. 40g of titanium dioxide and 10g of nano-SiO2 were added to 20g of deionized water and dispersed at 3000rpm for 20min. Then, 150g of fluorinated emulsion, 6g of film-forming aid Texanol, and 0.25g of defoamer BYK-028 were added sequentially and stirred at low speed. 0.7g of hydroxyethyl cellulose was added to adjust the viscosity. 0.25g of defoamer and 22.8g of deionized water were added, stirred, and then filtered through a filter to remove gel particles, thus obtaining a high-weather-resistant fluorinated acrylic composite coating.

[0079] Experimental Example 1

[0080] The yields of Examples 1 to 3 are shown in Table 1 below.

[0081] Table 1: DFMAET Yield Statistics

[0082]

[0083] As shown in Table 1, Example 1 represents the optimal synthesis parameter scheme for ethyl 2-difluoromethyl acrylate (DFMAET), which has a higher yield.

[0084] Experiment Example 2

[0085] QUV accelerated aging test includes the following steps:

[0086] Aluminum plates measuring 150mm × 70mm × 1mm were coated with the coatings from Examples 4-6 and Comparative Examples 1-4 (dry film thickness 60±5μm). Aluminum plates coated with the coating from Comparative Example 3 were baked in an oven at 150℃ for 30 minutes, while other coatings were cured at room temperature for 7 days. Three parallel samples were prepared. A QUV aging tester, equipped with a UVA-340 lamp, was used for ultraviolet irradiation (60℃, irradiance at 340nm 1.0W / m²). 2 2000h. Samples were removed every 200h, and the surface was cleaned with ethanol. The gloss was measured using a 60° gloss meter; the initial gloss value G0 and the gloss value after aging were recorded. t Calculate G t / G0×100%. Colorimeter measurement was used; ΔE > 3 was considered a significant discoloration. Defects such as cracks, powdering, and peeling were observed using a stereomicroscope. The results are shown in Table 2 below.

[0087] Table 2: Comparison of QUV accelerated aging tests

[0088]

[0089] As shown in Table 2, the coatings obtained by copolymerizing 2-difluoromethyl ethyl acrylate (DFMAET) and trifluoroethyl methacrylate (TFEMA) exhibit stronger UV absorption than those obtained by copolymerizing 2-difluoromethyl ethyl acrylate (TFEMA) and 2-methyl ethyl acrylate. The α-position fluorine provides more efficient short-range protection (UV absorption) than the β-position long-range protection. The gloss retention rate after 2000 hours exceeds 90%, far surpassing coatings prepared from TFEMA and 2-methyl ethyl acrylate, and slightly exceeding that of PVDF coatings. However, the cost of the coatings prepared by this invention is significantly lower than that of PVDF coatings. The color difference after 2000 hours in Examples 4-6 is lower than that of other materials, with no chalking or cracking.

[0090] Experimental Example 3

[0091] Neutral salt spray testing includes the following steps:

[0092] 100mm×100mm×2mm galvanized steel sheets were coated with epoxy zinc-rich primer (50μm), and after 24 hours, coated with the coatings of Examples 4-6 and Comparative Examples 1-4 (dry film thickness 80±5μm). Steel sheets coated with the coating of Comparative Example 3 were baked in an oven at 150℃ for 30 minutes, while steel sheets with other coatings were cured at room temperature for 7 days. A salt spray chamber was used with a 5% NaCl solution at 35℃, and the salt spray deposition rate was 1-2 mL / (80cm²·h). Continuous spraying was performed for 1000 hours, with observations every 200 hours. Surface salt crystals were rinsed with deionized water. Rust grades: Grade 0 - no rust; Grade 10 - complete rust. Adhesion change was tested using the cross-cut test: Holding the cutting tool with the blade perpendicular to the test plate surface, a suitable spacing guide device was used to apply uniform force to the cutting tool, making 6 cuts at a uniform speed, spaced 1mm apart. The minimum cut length should be significantly longer than the width of the multi-blade tool. All cuts will leave marks or scratches on the substrate. However, the depth of the scratches on the substrate should be as shallow as possible. Place the center of the tape on the grid, parallel to a set of cut lines, and then press the tape flat in the grid area. During the operation, the tape should completely cover the grid. To ensure good contact with the coating, rub the tape firmly with your fingertips or nails. Within 5 minutes of applying the tape, hold the tape at the suspended end and peel it off smoothly over 0.5 to 1.0 seconds at an angle as close to 60 degrees as possible. Under good lighting conditions, carefully examine the cut areas of the test coating visually using normal or corrected vision, or, as agreed by both parties, a magnifying glass. During observation, rotate the test plate appropriately so that the observation and lighting of the test area are not limited to one direction. The adhesion degradation rate was calculated and classified into six levels from 0 to 5. Level 0: Completely smooth cut edges with no coating loss within the grid. Level 1: Minor coating loss at cut intersections, but the affected cross-cut area not exceeding 5%. Level 2: Coating loss at cut intersections and / or along the cut edges, with the affected cross-cut area exceeding 5% but not exceeding 15%. Level 3: Coating loss along the cut edges in large fragments, and / or partial or complete loss at different locations on the grid, with the affected cross-cut area exceeding 15% but not exceeding 35%. Level 4: Coating loss along the cut edges in large fragments, and / or partial or complete loss of some squares, with the affected cross-cut area exceeding 35% but not exceeding 65%. Level 5: Degrees exceeding Level 4. The results are shown in Table 3 below.

[0093] Table 3: Neutral Salt Spray Test

[0094]

[0095] According to the data in Table 3, after neutral salt spray testing, the coating of this invention showed a rust level of 0 after 1000 hours compared to other coatings, indicating low rust severity and almost no decrease in adhesion. The neutral salt spray test results of Examples 4-6 were similar to those of the PVDF coating in Comparative Example 3. However, PVDF relies on physical adsorption (requiring a special epoxy primer, adhesion level 2) and has weak adhesion to low surface energy plastics such as PE / PP. PVDF requires baking at 150℃ for 30 minutes, resulting in high energy consumption and limiting substrate selection (plastic melting, wood carbonization), making it only suitable for high-temperature resistant substrates such as metal curtain walls. Compared to coatings prepared from trifluoroethyl methacrylate (TFEMA) and ethyl 2-methacrylate, the coating prepared in this invention exhibits higher weather resistance, is less prone to rust, and shows less adhesion reduction. Compared to PVDF coatings, it has slightly higher performance, while offering lower prices and easier application, making it a novel high-weather-resistant fluorinated acrylic composite coating.

[0096] Experiment Example 4

[0097] Damp heat aging test, including the following steps:

[0098] Concrete slabs (150mm × 70mm × 5mm) were sanded with 80-grit sandpaper, cleaned with deionized water, and dried. They were coated with the coatings from Examples 4-6 and Comparative Examples 1-4 (dry film thickness 80±5μm). Concrete slabs coated with Comparative Example 3 were baked in an oven at 150℃ for 30 minutes, while concrete slabs with other coatings were cured at room temperature for 7 days. They were then placed in a constant temperature and humidity aging chamber at 50℃ and 95% relative humidity for 1000 hours, with samples taken every 200 hours for testing. Additional samples were prepared, with the surface inoculated with a suspension of Aspergillus niger spores (concentration 10). 6 The samples (CFU / mL) were placed in a mold incubator (28℃, RH 95%) and cultured for 28 days. They were then soaked in deionized water for 24 hours, and the water absorption rate was calculated by weighing (results shown in Table 4). Adhesion changes were detected using the cross-cut test, the same method as in Experiment 3 (results shown in Table 5). After the incubation period, the samples were removed from the mold incubator and visually inspected first. When the moldy area was less than 10%, the samples were observed under a microscope at 50x magnification. Samples with 0% moldy area were classified as having a mold resistance grade of 0; samples with <10% moldy area were classified as having a mold resistance grade of 1; samples with >10% and <30% moldy area were classified as having a mold resistance grade of 2; samples with >30% and <60% moldy area were classified as having a mold resistance grade of 3; samples with ≥60% moldy area were classified as having a mold resistance grade of 4 (results shown in Table 6).

[0099] Table 4: Changes in water absorption rate (%)

[0100]

[0101] Table 5: Adhesion Grades

[0102]

[0103] Table 6: Mold Growth Levels

[0104]

[0105] Table 4 shows that the α-difluoromethyl group in the coating of this invention reduces surface energy and decreases initial water adsorption; the GMA epoxy cross-linking network blocks water diffusion, resulting in a lower increase in water absorption rate compared to TFEMA and 2-methyl-ethyl acrylate coatings. Although the water absorption performance of the fluorinated acrylic composite coating of this invention is not as good as that of PVDF coating, PVDF coating requires high-temperature baking during use, increasing its application difficulty. Table 5 shows that the fluorinated acrylic composite coating of this invention exhibits stable bonding and no decrease in adhesion under humid and hot conditions. PVDF coating relies on the physical adsorption of the epoxy primer; the PVDF layer itself is hydrophobic, making it difficult for water to penetrate the interface, and it remains stable after aging. However, the physical adhesion is weaker than the chemical adhesion of this invention. Table 6 shows that the fluorinated acrylic composite coating of this invention has low surface energy, preventing effective adsorption of spores; the chemical inertness of PVDF further inhibits mold metabolism, achieving a level 0 anti-mold rating. In contrast, other comparative coatings have high surface energy, and their porous structures become a mold culture medium after water absorption, easily leading to mold growth.

[0106] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the technical principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A high-weather-resistant fluorinated acrylic composite coating, characterized in that, A fluorinated emulsion is obtained by polymerizing ethyl 2-difluoromethyl acrylate, methyl methacrylate, butyl acrylate, and glycidyl methacrylate; the highly weather-resistant fluorinated acrylic composite coating is prepared by using the fluorinated emulsion, titanium dioxide, nano-SiO2, film-forming aid, defoamer, and thickener. The mass ratio of ethyl 2-difluoromethyl acrylate, methyl methacrylate, butyl acrylate and glycidyl methacrylate is (4-6):(6-8):(4-6):(2-4); The structure of the 2-difluoromethyl-ethyl acrylate monomer is as follows: 。 2. A method for preparing the high weather-resistant fluorinated acrylic composite coating according to claim 1, characterized in that, The preparation of ethyl 2-difluoromethyl acrylate includes the following steps: S1. Equipped with a four-necked flask including a mechanical stirrer, condenser, and constant pressure dropping funnel, with nitrogen protection throughout the process; S2. Dissolve ethyl acrylate in tetrahydrofuran, add to a four-necked flask, cool in an ice bath, add NaH, and stir until the bubbles completely disappear to form sodium α-enol intermediate; S3. Add difluoromethyl bromide through a dropping funnel. After the addition is complete, allow the temperature to rise naturally to reflux. Monitor the reaction endpoint by TLC to obtain the reaction solution. S4. After cooling the reaction solution, quench it with saturated ammonium chloride solution, extract with dichloromethane, combine the organic phases, dry with anhydrous sodium sulfate, filter, and remove the solvent by vacuum distillation to obtain the crude product; pass the crude product by silica gel column chromatography, collect the fraction with Rf=0.5, and distill under vacuum to obtain ethyl 2-difluoromethyl acrylate.

3. The method for preparing the high weather-resistant fluorinated acrylic composite coating according to claim 2, characterized in that, In S2, the molar ratio of ethyl acrylate to NaH is 1:(1-1.5); the ratio of tetrahydrofuran to ethyl acrylate is (45-55) mL:100 mmol; and the ice bath is used to cool the temperature to -5 to -15°C.

4. The method for preparing the high weather-resistant fluorinated acrylic composite coating according to claim 2, characterized in that, In S3, the molar ratio of difluoromethyl bromide to ethyl acrylate is (1-1.2):1; difluoromethyl bromide is dissolved in an equal amount of tetrahydrofuran as in S2; the addition flow rate is 0.3-0.7 mL / min; the reflux temperature is 60-70℃, and the reaction time is 10-18 h; the TLC monitoring uses petroleum ether and ethyl acetate as the developing solvent, with a volume ratio of petroleum ether to ethyl acetate of (4-8):1, a product Rf of 0.5, and a starting material Rf of 0.7; the reaction endpoint is the disappearance of the substrate spot, with only the product spot remaining.

5. The method for preparing the high weather-resistant fluorinated acrylic composite coating according to claim 2, characterized in that, In S4, the amount of saturated ammonium chloride solution added is 150-300 mL per 100 mmol of ethyl acrylate; the amount of dichloromethane used each time is 50-75 mL per 100 mmol of ethyl acrylate; anhydrous sodium sulfate is used for drying for 4-8 hours; the silica gel is 200-300 mesh; the eluent is petroleum ether and ethyl acetate, and the volume ratio of petroleum ether to ethyl acetate is (6-10):

1.

6. The method for preparing a high weather-resistant fluorinated acrylic composite coating according to claim 2, characterized in that, Includes the following steps: T1. Add ethyl 2-difluoromethyl acrylate, methyl methacrylate, butyl acrylate, and glycidyl methacrylate to a beaker in a certain proportion and stir mechanically until they are mixed evenly to obtain a monomer mixture; dissolve DNS-86 and OP-10 in deionized water and disperse ultrasonically until transparent to obtain an emulsifier aqueous solution; add the monomer mixture to the emulsifier aqueous solution and stir to form a stable pre-emulsion; T2. A four-necked flask is equipped with a stirrer, a condenser, a dropping funnel, and a thermometer. The flask is purged with nitrogen three times. The first portion of the preemulsion, the first portion of the ammonium persulfate solution, and deionized water are added to the flask. The mixture is heated and stirred. When the system shows a blue light, the second portion of the preemulsion and the second portion of the ammonium persulfate solution are added dropwise simultaneously. T3. After the addition is complete, keep the reaction at the temperature. After cooling, adjust the pH with ammonia water and remove trace amounts of unreacted monomers by vacuum distillation to obtain a fluorinated emulsion. T4. Add titanium dioxide and nano-SiO2 to the first part of deionized water, disperse in a high-speed disperser, add fluorinated emulsion, film-forming aid and the first part of defoamer in sequence and stir, add thickener to adjust viscosity, add the second part of defoamer and the second part of deionized water, stir and filter through a filter screen to remove gel particles, and obtain a high weather-resistant fluorinated acrylic composite coating.

7. The method for preparing the high weather-resistant fluorinated acrylic composite coating according to claim 6, characterized in that, In T1, the mechanical stirring rate is 300-800 rpm, and the time is 8-15 min; the mass ratio of DNS-86 to ethyl 2-difluoromethyl acrylate is 1:(10-15); the mass ratio of DNS-86 to OP-10 is 1:(0.2-0.6); the stirring speed is 1500-2500 rpm, and the time is 30-50 min.

8. The method for preparing the high weather-resistant fluorinated acrylic composite coating according to claim 6, characterized in that, In T2, the mass ratio of the first preemulsion, deionized water, and the first ammonium persulfate solution is 5:(6-10):(0.25-0.5); the first ammonium persulfate solution is an aqueous solution with a mass concentration of 2-4%; the temperature is raised to 70-80℃ at a rate of 5℃ / min; the stirring speed is 200-400 rpm; the mass ratio of the second preemulsion and the second ammonium persulfate solution is 6:(0.7-1.4), and the dropping rate of the second preemulsion is 1-3 mL / min; the second ammonium persulfate solution is an aqueous solution with a mass concentration of 2-4%, and the dropping rate of the second ammonium persulfate solution is 0.5-1.5 mL / min.

9. The method for preparing the high weather-resistant fluorinated acrylic composite coating according to claim 6, characterized in that, In step T3, the heat preservation temperature is 80-90℃ and the time is 1-2 hours; the temperature after cooling is 35-45℃; the ammonia water is an aqueous solution with a mass concentration of 5-15% and the pH is adjusted to 8.5; the vacuum distillation is carried out under the conditions of -0.08MPa and 35-45℃.

10. The method for preparing the high weather-resistant fluorinated acrylic composite coating according to claim 6, characterized in that, In T4, the mass ratio of titanium dioxide, nano-SiO2, and the first portion of deionized water is (7-9):(1-3):(3-5); the high-speed disperser operates at 2000-4000 rpm for 15-25 min; the mass ratio of the fluorinated emulsion, film-forming aid, and the first portion of defoamer is 150:(5-6):(0.2-0.3); the stirring speed is 300-800 rpm; the thickener is hydroxyethyl cellulose, and the mass ratio of hydroxyethyl cellulose to the fluorinated emulsion is (0.5-1.0):150; the second portion of defoamer is equal to the first portion of defoamer; the mass ratio of the second portion of deionized water to the fluorinated emulsion is (19.1-26.4):150; and the filter screen is 100 mesh.

Citation Information

Patent Citations

  • Preparation method and application of nano silicon dioxide-fluorine-containing polyacrylate composite matting agent

    CN112831239A

  • Pattern-forming method and directed self-assembling composition

    US20150252216A1